A Fluorescent Probe Based on Polyethyleneimine Protected Copper Nanoclusters for the Assay of Tetracycline Hydrochloride and Vitamin B12. Issue 40 (25th October 2021) - Yu, Weihua; Qin, Yongjun; Fan, Yucong; Wang, Zhonghua; Cheng, Zhengjun
Abstract: A water‐soluble and polyethyleneimine protected copper nanoclusters (CuNCs@PEI) was prepared by one‐step ultraviolet radiation (UVI) combined with microwave heating (MWH) method, and the influence of different energy suppliers on the CuNCs@PEI luminescence performance was investigated in detail. The as‐prepared CuNCs@PEI could be used as a viable fluorescent probe for sensitive and selective mensurating TCH (tetracycline hydrochloride)/VB12 (vitamin B12) with a linear response in the range of 0.33–66.67/0.33‐53.33 μmol L −1, and corresponding limit of detection (LOD) and limit of quantification (LOQ) were calculated to be 55.50/56.34 and 184.82/187.61 nmol L −1 . The fluorescence (FL) quenching of CuNCs@PEI by TCH/VB12 came from the combination of FRET (Förster resonance energy transfer) and IFE (inner filter effect). Moreover, the probe was successfully extended to the assays of TCH in veterinary powder or TCH tablets and VB12 in oral liquid or VB12 tablets with satisfactory results compared to the standard HPLC method. Besides, the CuNCs@PEI probe exhibited a good temperature sensing. Abstract : A water‐soluble and stable polyethyleneimine protected copper nanoclusters (CuNCs@PEI) was prepared by one‐step ultraviolet radiation (UVI) combined with microwave heating (MWH) method. Subsequently, a new and simple CuNCs@PEI probe could be used for sensitively and selectively monitoring TCH (tetracycline hydrochloride)/VB12 (vitamin B12). In addition, the probe was extended to the assay of TCH/VB12 in actual samples.